‘Appropriate’ medical treatment: what’s in a word? - Phull, Jaspreet; Bartlett, Peter (RSM Press, 2012)
Following the amendments in the 2007 Act, there were several revisions made focusing largely on community treatment orders and deprivation of liberty of persons lacking capacity. One of the amendments included a requirement that ‘appropriate treatment’ be ‘available’ for compulsion to be imposed in a variety of contexts, most notably admission for treatment under section 3. The definition of appropriate medical treatment within the Act appears largely circular, and therefore of little assistance. The Code of Practice provides some guidance but does little to add to the statutory language. In terms of jurisprudence, there are three reported cases concerning the provision. These cases are analysed and their significance is discussed in an attempt to formulate a clearer definition for appropriate medical treatment.